Hannah Arendt: thinking the education crisis in the contemporary world (Educação e Pesquisa, 2010)
Comprised of three complementary parts, the present article discusses Hannah Arendt's reflection on the education crisis in the contemporary world. In the first part general theoretical connections are established between Arendt's theses on the education crisis and her philosophical-political thinking about the political crisis of modernity. The second part of the text discusses the Arendtian hypothesis that the education crisis is also related to the introduction of educational approaches of a psychopedagogical character which, instead of contributing to educate the young to the responsibility for the world and for political action, keep them in a childlike condition that lasts up to adulthood, consequently bringing new political problems. Finally, in the third part of the text, the hypothesis is proposed that one of the main contributions from Arendt's thinking to the reflection about the contemporary crisis of education can be found in her fruitful discussion of the "critique"-"crisis" pair, which brings into question the traditional "crisis/reform" couple. Arendt, similarly to Foucault and Deleuze, teaches us that critique and crisis are inseparable modern phenomena, and invites us to see crisis as a privileged moment for the exercise of the activity of critique. For Arendt, the education crisis should be understood as a crucial opportunity for critical reflection about the education process itself.